Optimalisasi Pemasaran Digital sebagai Strategi Utama Meningkatkan Daya Jual dan Pertumbuhan UMKM - Budi Prasetiyo; Yogi Suprayogi; Arry Widodo (Jurnal Informasi Pengabdian Masyarakat, 2024)
The training titled “Optimizing Digital Marketing as the Main Strategy to Increase Sales and Growth of MSMEs” is expected to serve as a solution to enhance the understanding and competencies of MSMEs, particularly in digital marketing, thereby increasing their sales and fostering growth. Additionally, MSMEs are anticipated to act as a pathway to improve the welfare of many (suppliers, retailers, partners, etc.). This training program is essential to equip Q-Creative members with the digital skills needed to compete in the modern market. In an era increasingly dominated by technology, digital marketing has become one of the keys to MSME success. Through this training, community members will learn how to manage social media, create engaging marketing content, and utilize e-commerce platforms to expand their market reach. This initiative aims to help them reach a wider audience, boost sales, and optimize their marketing strategies. This community service program also supports the Sustainable Development Goals (SDGs), a global action plan endorsed by world leaders (193 countries), including Indonesia, committed to ending poverty, reducing inequality, and protecting the environment. The SDGs program is a sustainable development agenda with 17 goals and 169 targets. One of the objectives of this community service activity is to achieve quality education that improves human welfare globally.